Analisis Semiotika Nilai Gotong Royong Tayangan Bocah Petualang Di Televisi Trans 7 (Analisis Semiotika Roland Barthes Dalam Tayangan Bolang Edisi Kabupaten Lahat Sumatera Selatan) - Dori Dramika; Sri Narti; Harius Eko Saputra (UNIVED PRESS, Universitas Dehasen Bengkulu, 2017)
This study to detennine the meaning contained in the show adventurous child edition of Labat Regency South Sumatra on Television. The research method used in this research is semiotic analysis method using semiotik analysis of roland barthes. Divided by the meaning of denotation, connotation and myth. The analysis shows that there is meaning of semiotic analysis according to Roland Barthes. The Meaning of Denotation on the show of Bocah Petualang The edition of Labat regency of South Sumatra is the location where they are shooting is an unspoiled forest seen from the number of green trees that grows flourish and shade. The river is still Asri and not contaminated by the number of fish catches. Meaning of connotation in the show Bocah Petualang Edition of Labat regency of South Sumatra is to explain that children who are very devoted to their parents and also loyal friends. Myths in the show Bocah Petualang The edition of Labat regency of South Sumatra is a smoke that can make bees become tame and not bite. Ash which can make Rang-Rang ants become tame and does not bite. And Reverse the clothes that can make someone fmd a way out when lost. The myth is merely a belief that is believed to be descended only but as human beings we may believe it may not. Value gotong royong contained in the show Bocah Adventurers Edition of Labat regency of South Sumatra is the Children who always together mutually help-help to fmish a job together.